Genome-Wide Analysis of U-box E3 Ubiquitin Ligase Family in Response to ABA Treatment in Salvia miltiorrhiza - Chen, Chengan; Wang, Can; Li, Junbo; Gao, Xiankui; Huang, Qikai; Gong, Yifu; Hao, Xiaolong; Maoz, Itay; Kai, Guoyin; Zhou, Wei (Frontiers in Plant Science, 2022)
Several biological processes and responses to stressors in plants reveal the involvement of a family of ubiquitin ligases (E3) called Plant U-box (PUB) proteins. However, in Salvia miltiorrhiza, the various aspects of the entire genome and differences in functionality of the gene family of the U-box E3 (UBE3) ubiquitin ligases continue to remain quite obscure. The 60 UBE3 genes in the S. miltiorrhiza genome were recognized in the present study. Here, the gene structure, motifs and promoters were examined, in addition to their physical and chemical qualities. Based on the phylogenetic relationship, the 60 UBE3 genes could be categorized under six different groups. The highly conserved domains within the UBE3 gene family were identified in S. miltiorrhiza. On analyzing the cis-acting element it was evident that the UBE3 genes could have a role to play in an assortment of biological processes, e.g., as a reaction to the abscisic acid (ABA) treatment. This hypothesis was examined by designing an ABA treatment to the hairy root of S. miltiorrhiza. Post the ABA treatment significant up-regulation was observed in thirteen of the UBE3 genes. The findings of the present study brought fresh and new understanding to the participation of the UBE3 gene family in plants, specifically in their biological responses mediated by the ABA. In S. miltiorrhiza, this gene family may be crucial during the ABA treatment. Significantly, the results arising from this study offer novel data to enhance the understanding of the ubiquitin ligase genes and their functionality in plants.